Case Report Study on the Integrated Management of Sickle Cell Patient with Re-Infection of COVID-19 - Desai, Atul; Desai, Kavita; Desai, Hemshree; Desai, Rutvij; Desai, Chirag; Desai, Saloni (Indian Journal of Pharmacy Practice)
The entire world has been impacted and devastated by coronavirus infection. Coronavirus infection requires no more introductions. Sickle cell patients are more prone to coronavirus infection and its complications. There is plenty of research done on the management of coronavirus infections, options and combinations initially found effective, but at the end of 2nd year revealed no potential benefit. An integrated treatment approach always becomes a possible option in the management of any complications. The case study mentioned here provides information about integrated treatment in patients of sickle cell anemia re-infected with coronavirus infection presented with positive RT-PCR, HRCT score 03/25 with moderate hepatomegaly, gall bladder sludge and auto splenectomy. The patient was previously infected with coronavirus and recovered completely with integrated treatment. He had received his vaccination for coronavirus. The patient was re-infected with coronavirus infection and developed sickle cell crisis complications for which he was hospitalized. Despite continuous monitoring SpO2 (78%) was dropping, after discussion with family members a patient was shifted to clinic from hospital. With prior knowledge and consent, the 300 mg T-AYU-HM Premium along with integrated treatment was initiated. There was an observational improvement in clinical conditions and oxygen saturation was restored to 95% within five days. Post-discharge, he adhered to treatment and recovered from clinical complications like hepatomegaly. This approach was economical, safer and therapeutically effective. Further well-organized studies are requires to evaluate the effectiveness of the integrated treatment approach.
Keywords: Autospelenectomy; Hepatomegaly; HRCT; COVID-19; T-AYU-HM Premium